Hybrid treatment of aortic valve regurgitation and right heart failure 22 years after heterotopic heart transplantation. (30th October 2018) - Smail, Hassiba; Stock, Ulrich; Simon, Andre
Abstract: Clinical application of heterotopic heart transplantation is no longer pursued. However, a significant number of patients present again with deteriorating function of the native or recipient's heart. We describe the management of severe native aortic regurgitation and right heart failure in a patient following heterotopic heart transplantation. We performed a percutaneous closure of the insufficient native aortic valve followed by a surgical transposition of the donor's pulmonary artery from the recipient's right atrium to the pulmonary artery.